Comparison of exhaled carbon monoxide levels and its association with nicotine dependence between electronic and tobacco cigarettes: A cross-sectional study among teenage smokers - Raffael, Frans; Pandia, Pandiaman; Tarigan, Amira P.; Mutiara, Erna; Osakue, Osareniro E. (Narra Sains Indonesia, 2023)
Carbon monoxide (CO), resulting from incomplete combustion such as tobacco smoking, serves as an indicator of nicotine addiction. The aim of this study was to compare the levels of exhaled CO levels between electronic cigarette (e-cigarette) and tobacco smokers and to determine the association between nicotine dependence and exhaled CO levels in e-cigarette and tobacco smokers. A cross-sectional study was conducted using purposive sampling on active smokers, with 70 smokers in each group. The nicotine dependence was measured using the Penn State Nicotine Dependence Index (PSNDI) questionnaire for the e-cigarette group and the Fagerstrom questionnaire for the tobacco smoking group. The CO level was measured using the smokerlyzer piCO. To compare the mean exhaled CO levels between e-cigarettes and tobacco smoker groups, the Mann-Whitney test was used. The Mann-Whitney test and Kruskal-Wallis test were used to assess the associations between nicotine dependence and mean exhaled CO levels in the e-cigarette smoker group and in the tobacco smoker group, respectively. The majority of e-cigarette smokers were 17 years old (65.7%) and male (75.7%). Among tobacco smokers, the majority were also 17 years old (44.3%), and mostly male (91.4%). The mean exhaled CO levels in the tobacco smoker group were significantly higher than the e-cigarette smoker group, 6.86 ppm vs 1.61 ppm with p<0.001. There was a significant association between nicotine dependence and exhaled CO levels among tobacco smokers (p<0.001). Nicotine dependence was not associated with exhaled CO levels among e-cigarette smokers. This study highlights that the smokerlyzer piCO devise could be used to screen nicotine addiction in tobacco smokers.